An examination of ankle joint position sense, postural control and associated neuromuscular deficits in patients with plantar fasciitis: a cross-sectional analysis with advanced biomechanical and psychosocial correlates - Shaker Hassan S. Alshehri; Mastour Saeed Alshahrani; Saeed Y. Al Adal; Faisal M. Alyazedi; Hani Hassan Alnakhli; Ravi Shankar Reddy (Journal of Orthopaedic Surgery and Research)
Abstract Background Ankle joint position sense (AJPS) accuracy and postural control are crucial for maintaining balance and stability, particularly in individuals with plantar fasciitis who may experience proprioceptive and functional impairments. Understanding how psychosocial factors, such as pain catastrophizing, and biomechanical measures, like muscle strength and gait parameters related to proprioception and postural control, can inform more effective treatment approaches. This study aimed to (1) examine the relationship between AJPS accuracy and biomechanical factors—including postural stability, lower limb muscle strength, and gait parameters—in individuals with plantar fasciitis d (2) analyze the impact of psychosocial factors, including pain catastrophizing, physical activity level, and quality of life, on AJPS accuracy and postural control in this population. Methods A total of 126 participants (63 with plantar fasciitis and 63 controls) were recruited. AJPS was assessed using a digital inclinometer across four movement directions (plantarflexion, dorsiflexion, inversion, eversion). Postural stability metrics (antero-posterior and medio-lateral sway) were measured using computerized posturography, while muscle strength in plantar flexors, dorsiflexors, inverters, and evertors was assessed with a hand-held dynamometer. Gait parameters (step length, cadence, stance time) were captured via 3D motion capture. Pain catastrophizing, physical activity, and quality of life were evaluated using validated questionnaires (PCS, IPAQ, FHSQ). Results Significant differences were observed in AJPS accuracy between groups, with plantar fasciitis patients showing higher AJPS error in plantarflexion (mean difference = 1.22°, p < 0.001) and dorsiflexion (mean difference = 1.31°, p < 0.001). Pain catastrophizing was a significant predictor of AJPS in plantarflexion (β = -0.05, p = 0.001). Postural stability was negatively correlated with AJPS accuracy, particularly in mediolateral sway (r = -0.32, p = 0.037), while physical activity and quality of life had minimal effects. Conclusion This study highlights the impact of pain catastrophizing on proprioceptive deficits in plantar fasciitis, emphasizing the importance of addressing psychological as well as biomechanical factors in treatment. Integrating cognitive-behavioral strategies may enhance proprioceptive accuracy and stability outcomes in this population.